A case presentation on rare case of retroperitoneal liposarcoma - Patel, Soham H.; Patel, Aakash N.; Malek, Tanveer N.; Kuswaha, Manoranjan R. (International Surgery Journal, 2023)
Retroperitoneal liposarcoma is a rare biologically heterogeneous tumor that present considerable challenges due to its size and deep location.as consequences, the majority of the patients with high grade rpls will develop locally recurrent disease following surgery, and this constitutes the cause of death in most patients. Symptoms are usually nonspecific and they do not appear until the tumor becomes very large. Early diagnosis is difficult as there is an absence of specific clinical presentations. A painless abdominal lump that enlarges in a long period of time in an adult is the most common history of patient. Metastasis at initial presentation is uncommon. Surgical exploration is needed for the final pathological diagnosis. Case presentation: we report a case of 56 year old male patient who underwent a complete surgical excision of pleomorphic retroperitoneal liposarcoma. Retroperitoneal liposarcomas are rare soft tissue sarcoma. They often cause minimal or no symptoms and can reach a significant size, growing undetected in retroperitoneal space before invading or compressing surrounding organs, eventually leading to clinical symptoms. Complete surgical excision is the mainstay of treatment. Whenever possible, macroscopically complete resection should be aimed at, often requiring en bloc removal of adjacent structures such as the abdominal wall, psoas, or paravertebral muscles.